(untitled) (Journal of Medicine, 2009)
Tuberculosis (TB) is a major public health problem of increasing proportions in Bangladesh for last several decades. A total of 350,641 cases were reported in Bangladesh in 2006 representing an incidence of 225 per 100,000 population for that year. Many hematological derangements such as anaemia, leukocytosis or pancytopenia can occur in association with TB. However isolated thrombocytopenia is rare and most commonly occur via a non immune mechanism in the setting of pancytopenia that develop secondary to granulomatous infiltration of the bone marrow. Â However immune thrombocytopenic purpura (ITP) in a patient with TB is exceedingly a rare event. Here we report a case of ITP associated with TB of knee joint in whom thrombocytopenia and TB were successfully treated. A casual association between joint TB and ITP is extraordinarily rare and to our knowledge this is the first such case documentation in Bangladesh, although a few case reports citing association of TB and ITP are found in literature. Â doi:10.3329/jom.v10i1.2001 J Medicine 2009; 10: 28-30